Semi-Solid Processing of Alloys and Composites - Nafisi, Shahrooz; Ghomashchi, Reza (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Semi-solid metal (SSM) processing, as a viable alternative manufacturing route to those of conventional casting and forging, has not yet been fully exploited despite nearly half a century since its introduction to the metal industry. The slow pace of adopting SSM routes may be due to various reasons, including capital costs, profit margins, and, most importantly, the lack of detailed analysis of various SSM processes in open literature to confidently establish their advantages over more conventional routes. Therefore, the SSM community must disseminate their findings more effectively to generate increased confidence in SSM processes in the eyes of our industrial leaders. As such, we have embarked on the task to invite the leaders in SSM research to share their findings in a Special Issue dedicated to semi-solid processing of metals and composites. SSM processing takes advantage of both forming and shaping characteristics usually employed for liquid and solid materials. In the absence of shear forces, the semi-solid metal has similar characteristics to solids, i.e., easily transferred and shaped; by applying a defined force, the viscosity is reduced and the material flows like a liquid. These unique dual characteristics have made SSM routes attractive alternatives to conventional casting on an industrial scale. With the intention of taking full advantage of SSM characteristics, it is crucial to understand SSM processing, including topics such as solidification and structural evolution, flow behavior through modelling and rheology, new processes and process control, alloy development, and properties in general. This Special Issue focuses on the recent research and findings in the field with the aim of filling the gap between industry and academia, and to shed light on some of the fundamentals of science and technology of semi-solid processing.